Innovation in technology-based creative industries - Fitri Fitri; Dewi Anggraeni; Wahyu Hidayat; M. Noor Anzali (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to explain the importance of innovation strategies in efforts to improve corporate performance and the competitive advantage of technology-based creative industries. The descriptive qualitative approach is used in this study to analyze technology-based innovative industrial entrepreneurs. Using the snowball technique to collect responders or informants. In-depth interviews, observation, and documentation studies were used to collect data. After collecting data in the field, the data will be validated using data source triangulation techniques. Qualitative data was processed in three stages: data reduction, data presentation, and conclusion drafting. According to the findings of the study, technology-based creative entrepreneurs are open to new ideas and concepts in building the company's business and have made innovation a part of their business strategy. However, only a small percentage of respondents made investments to grow their businesses